(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The investigation of present enrolment, drop out andattendance trends for scheduled caste and scheduled tribes children is preventedby absence of complete and similar statistical data. The major sources whichhave been acquired are the Census, HRD Statistical Publications of theMinistry, Commissioner Reports, the NSSO and Commission for scheduled castesand scheduled tribes (Nambissan, Geetha, 2000; Sujatha, 1987, 1994, 1996, 2002;Aggarwal Yash & Sibou, Sarika, 1994; Chatterjee, 2000). The literacysituation offers a rough indication of overall progress of education as well asserves as an index of past opportunity of education. The below table shows thegains of literacy during 1991-2001 among different categories of demography: